Cellular, Hormonal, and Behavioral Responses of the Holothuroid Cucumaria frondosa to Environmental Stressors - Jobson, Sara; Hamel, Jean-François; Hughes, Taylor; Mercier, Annie (Frontiers in Marine Science, 2021)
Holothuroids (sea cucumbers) are one of the most ubiquitous groups of benthic animals found across diverse marine ecosystems. As echinoderms, they also occupy an important place in the evolutionary hierarchy, sitting close to vertebrates in the deuterostome clade, making them valuable multidisciplinary model organisms. Apart from being ecologically and phylogenetically important, many species are commercially exploited for luxury seafood markets. With the global rise of aquaculture and fisheries, management and protection of these valuable species relies on a better understanding of how their immune systems respond to environmental and anthropogenic stressors. Here, the cellular, hormonal and behavioral indicators of stress in the North Atlantic sea cucumber Cucumaria frondosa were examined. The immediate and carry-over (post recovery) effects of a 1-hour exposure to low salinities or to emersion (at two temperatures) highlighted that morphoplasticity in C. frondosa was accompanied by shifts in all monitored indicators. From baseline levels measured in controls, densities of free coelomocytes increased, showing successions of specific cell types and subsequent coelomocyte aggregations, combined with a rise in cortisol levels. These responses mirrored increased fluctuations in cloacal opening rates, decreased force of attachment to the substrate, and enhanced movements and active buoyancy adjustment with increasingly severe stressors. The findings suggest that many systems of sea cucumbers are impacted by stresses that can be associated with harvesting and handling methods, with likely implications for the quality of the processed products. Gaining a deeper understanding of immune and hormonal responses of sea cucumbers is not only of broad ecological and evolutionary value, but also helpful for the development of sustainable fisheries and aquaculture practices, and conservation programs.